Robot-Assisted Laparoscopic Partial Adrenalectomy for Pheochromocytoma: The National Cancer Institute Technique - Asher, Kevin P. (2011)
BACKGROUND: Partial adrenalectomy has recently been advocated to preserve unaffected adrenal tissue during resection of pheochromocytoma. OBJECTIVE: To describe a robot-assisted laparoscopic partial adrenalectomy (RALPA) technique and to report on early functional and oncologic outcomes. DESIGN, SETTING, AND PARTICIPANTS: From 2007 to 2010, 15 RALPA were performed on 12 consecutive patients with pheochromocytoma. Follow-up data of >1 yr are available on 11 procedures. Median follow-up for the entire cohort was 17.3 mo (range: 6–45). SURGICAL PROCEDURE: Positioning and port placement is designed for adequate reach and visualization of the upper retroperitoneum. The plane between the adrenal cortex and pheochromocytoma pseudocapsule is identified visually and with laparoscopic ultrasound. The tumor is dissected away from normal adrenal cortex, preserving normal adrenal tissue. MEASUREMENTS: Preoperative, perioperative, pathologic, and functional outcomes data were analyzed. RESULTS AND LIMITATIONS: Fourteen of 15 cases were completed robotically. Among 15 procedures, 4 were performed on a solitary adrenal gland. Four cases required resection of multiple tumors (up to six) with two performed in a solitary gland. The mean age of the patients was 30 yr, and the mean body mass index was 27. The mean operative time was 163 min, the median estimated blood loss was 161 ml, and the median tumor size was 2.7 cm (range: 1.3–5.5). There was one conversion to an open procedure in a patient requiring reoperation on a solitary adrenal gland. One patient who underwent RALPA on a solitary adrenal gland required postoperative steroid supplementation at last follow-up. At a median follow-up of 17.3 mo (range: 6–45), there were no recurrences or metastatic events. Study limitations include small sample size and short follow-up. CONCLUSIONS: RALPA for the treatment of pheochromocytoma is feasible and safe and provides encouraging functional and oncologic outcomes, even in patients with a solitary adrenal lesion or multiple ipsilateral lesions.